THE DEVELOPMENT OF SUSTAINABLE RESERVE FOOD GARDEN PROGRAM’S VIDEO IN MALANG CITY - Benny Satria Wahyudi; Mimien H. I Al-Muhdhar; Sueb Sueb; Susilowati Susilowati; Endang Budiasih (UPT Penerbitan Universitas Jember, 2016)
Abstract—Food security is a priority to resolve hunger and malnutrition in society. One of the effort to increase food security and nutrition of family can be used with utilization of available resources and yard by households through the Sustainable Reserve Food Garden’s Program. The purpose of this research was to produce a Sustainable Reserve Food Garden Program’s video with valid citeria based on ASSURE development model and it can be used in large group. The small test group location of this research was conducted at Lowokwaru, Malang City. The data was obtained by using questionnare on March to May 2016. Questionnaire are validated by an expert. The data were analyzed by analysis of percentages. The results showed that average of instrumental experts, matter expert, a media expert, and an environmental practitioner validation get 84,96% with a very valid category. Average of small test group (video legibility test) in Lowokwaru is 88,75% with a very valid category. This research implies that video is valid and it can be used in large group.